Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1021/la904532s
|View full text |Cite
|
Sign up to set email alerts
|

AFM Investigations of Phase Separation in Supported Membranes of Binary Mixtures of POPC and an Eicosanyl-Based Bisphosphocholine Bolalipid

Abstract: Supported membranes prepared from binary mixtures of DOPC and the bolalipid C 20 BAS have been examined by atomic force microscopy (AFM). The supported membranes are phase separated to give a thicker DOPC-rich phase and a thinner bolalipid-rich phase for a range of lipid compositions. These results confirm an earlier prediction from mean field theory that phase separation is the thermodynamically stable state for membranes containing approximately equimolar C 20 BAS and double chain monopolar lipids with chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…47 Recently, we have concluded that the selection for a subset of vesicles from a heterogeneous vesicle population during bilayer formation may contribute to unexpected trends in morphology for bolalipid/POPC mixtures. 48 In the present study, the presence of the bromohydroxycoumarin moiety, which is partially deprotonated at the pH used to form SUVs and supported bilayers in our experiments, may be an important factor. Variations in the net negative charge on the SUVs due to different fractions of 1 coupled with electrostatic repulsion between the vesicles and the negatively charged surface could lead to the formation of a supported bilayer with a lower mole fraction of 1 than in the bulk vesicle suspension.…”
Section: ■ Discussionmentioning
confidence: 77%
“…47 Recently, we have concluded that the selection for a subset of vesicles from a heterogeneous vesicle population during bilayer formation may contribute to unexpected trends in morphology for bolalipid/POPC mixtures. 48 In the present study, the presence of the bromohydroxycoumarin moiety, which is partially deprotonated at the pH used to form SUVs and supported bilayers in our experiments, may be an important factor. Variations in the net negative charge on the SUVs due to different fractions of 1 coupled with electrostatic repulsion between the vesicles and the negatively charged surface could lead to the formation of a supported bilayer with a lower mole fraction of 1 than in the bulk vesicle suspension.…”
Section: ■ Discussionmentioning
confidence: 77%
“…47 Thus, the composition of MLVs formed during hydration of dry films depends on the region of the film hydrated. One might contend that sonication would robustly homogenize the mixture during SUV formation, but this has been shown not to be the case, 46 suggesting that MLVs have tremendously de-mixed compositions prior to SUV formation. Finally, one might suppose that in the last step of PLB preparation, where vesicles fuse to particle surfaces, dispersion of SUVs and coordinated fusion would better mix lipid components, but since only ~1000 SUVs of 100 nm diameter are required for fusion to a 5 µm-sized sphere, where suspensions of sonicated vesicles contain on the order of 10 12 – 10 13 SUVs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the kinetics of fusion are dependent on vesicle composition and size, where SUVs with more mobile components and greater elasticity will rupture and fuse rapidly after adsorption, but less mobile components require a significant amount of vesicle adsorption before rupture is initiated. 22, 46 This was probed in a recent spherically-supported biomembrane study using fusion with different sizes of starting lipid vesicles that resulted in differences in organization of lipids and shapes of co-existing domains. 39 Taken together, SUVs here are considerably heterogeneous and a difference in the rate of vesicle fusion further deters homogenization, leading to PLBs with different compositions within the L d /L o co-existence region and fractions of L d /L o content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Independently of their length, however, all WALP peptides were observed to increase domain alignment. The structural coupling mechanism is not confined to transmembrane proteins; it also applies to bolalipids [39] and even to lipids with long tails such as monosialotetrahexosylganglioside (GM1) [40] and other long saturated acyl chains [11] that interact with the lipids in the apposed leaflet.…”
Section: Introductionmentioning
confidence: 99%